MORSON, Gary Saul; EMERSON, Caryl. Mikhail Bakhtin: criação de uma prosaística. Tradução de Antonio de Pádua Danesi. São Paulo: Edusp, 2008. - Souza, Ester Maria de Figueiredo (Politeia - História e Sociedade, 2010)
.